2017
DOI: 10.1038/srep42190
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar Lavage Proteomics in Patients with Suspected Lung Cancer

Abstract: Lung cancer configures as one of the deadliest types of cancer. The future implementation of early screening methods such as exhaled breath condensate analysis and low dose computed tomography (CT) as an alternative to current chest imaging based screening will lead to an increased burden on bronchoscopy units. New approaches for improvement of diagnosis in bronchoscopy units, regarding patient management, are likely to have clinical impact in the future. Diagnostic approaches to address mortality of lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 51 publications
5
44
2
Order By: Relevance
“…Concerning the control group used, 5 studies used normal tissue collected during surgery from the same subjects, 8 used patients with pulmonary nodules or other comorbidities (i.e., chronic obstructive pulmonary disease, interstitial lung disease, bronchiectasis, heart failure, asthma, chronic cough, and pulmonary nodule [18] ), 6 did not indicate any control groups. Moreover, not all the studies indicated the patient smoking habits.…”
Section: Participants' Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the control group used, 5 studies used normal tissue collected during surgery from the same subjects, 8 used patients with pulmonary nodules or other comorbidities (i.e., chronic obstructive pulmonary disease, interstitial lung disease, bronchiectasis, heart failure, asthma, chronic cough, and pulmonary nodule [18] ), 6 did not indicate any control groups. Moreover, not all the studies indicated the patient smoking habits.…”
Section: Participants' Inclusion Criteriamentioning
confidence: 99%
“…For instance, bronchoalveolar lavage or pleural effusions, that are routinely used for disease staging in surgery, are too invasive for screening purposes. [18,89] Blood, exhaled breath condensate and urine are instead all easy to collect. The majority of the biomarker discovery research conducted in recent years has been devoted to the analysis of biomarkers isolated from serum or plasma, thanks to the fact that blood sampling can be carried out following a highly standardized method, reproducible, easy to perform worldwide, which is also applicable to the longitudinal analysis of samples, for tumor recurrence monitoring.…”
Section: Biological Sample Typementioning
confidence: 99%
“…BALF has its merit in that it can provide a variety of information including immunologic, inflammatory, and infectious processes that occur at the lung parenchyma . Recent studies have demonstrated potential usefulness of cancer‐associated proteins, nucleic acid, and extracellular vesicles in the BALF for early detection and molecular characterization of lung cancer …”
mentioning
confidence: 99%
“…A LC‐MS/MS approach allowed Carvalho et al. to study the proteomics of BALf in an observational cohort of 90 patients with suspected lung cancer (seven suspicious; 47 with no lung cancer suspicion, 36 lung cancer) undergoing diagnostic bronchoscopy. Diagnosis was based on both BAL cytology and tumor histology.…”
Section: Bodily Systems and Related Less‐conventional Fluidsmentioning
confidence: 99%